Construction and validation of the HeiQ: an operation-oriented figural matrices test - Pallentin, Vanessa S.; Danner, Daniel; Rummel, Jan (Journal of Intelligence, 2023)
Figural matrices tests are among the most popular and well-investigated tests used to assess inductive reasoning abilities. Solving these tests requires the selection of a target that completes a figural matrix among distractors. Despite their generally good psychometric properties, previous matrices tests have limitations associated with distractor construction that prevent them from realizing their full potential. Most tests allow participants to identify the correct response by eliminating distractors based on superficial features. The goal of this study was to develop a novel figural matrices test which is less prone to the use of response elimination strategies, and to test its psychometric properties. The new test consists of 48 items and was validated with N = 767 participants. Measurement models implied that the test is Rasch scalable, inferring a uniform underlying ability. The test showed good to very good reliability (retest-correlation: r = 0.88; Cronbach’s alpha: α = 0.93; split-half reliability: r = 0.88) and good construct validity (r = 0.81 with the Raven Progressive Matrices Test, r = 0.73 with global intelligence scores of the Intelligence Structure Test 2000R, and r = 0.58 with the global score of the Berlin Intelligence Structure Test). It even superseded the Raven Progressive Matrices Tests in criterion-related validity (correlation with final year high school grades (r = −0.49 p < .001)). We conclude that this novel test has excellent psychometric properties and can be a valuable tool for researchers interested in reasoning assessment.